Ultrasound based modification and structural-functional analysis of corn and cassava starch - Abdul Rahaman (Elsevier, 2021)
In this study, the starch molecules were modified with ultrasonication at two different time intervals by using starch molecules from corn and cassava. This research aimed to examine the effect of the high power ultrasound of 40 kHz voltage and frequency with short time duration on structural and physical properties of corn and cassava starch. Morphology of ultrasonically treated starch granules was observed by scanning electron microscopy (SEM), FTIR, differential scanning calorimetry (DSC), and X-ray diffraction (XRD) and compared with untreated samples. After the ultrasound treatment groove and notch appeared on the surface of the starch granules. The results showed that gelatinization temperature did not change with ultrasound treatments, but enthalpy value decreased from 13.15 ± 0.25 J/g to 11.5 ± 0.29 J/g and 12.65 ± 0.32 J/g to 10.32 ± 0.26 J/g for sonicated corn and cassava starches, respectively. The XRD results revealed a slight decreased in the crystallinity degree (CD) of sonicated corn (25.3,25.1) and cassava starch (21.0,21.4) as compared to native corn (25.6%) and cassava starch (22.2%). This study suggests that non-thermal processing techniques have the potential to modify the starch from different sources and their applications due to starch’s versatility, low cost, and comfort of use after processing with altered physicochemical properties.